Nurses’ knowledge and attitude towards children pain management: a multi-site survey study - Fenta, Efrem; Kibret, Simegnew; Hunie, Metages; Tamire, Tadese; Eshetie, Denberu; Seid, Shimelis; Fentie, Yewlsew; Amaha, Eleni; Desse, Tiruwork; Dejen, Bantayehu; Essa, Keder; Teshome, Diriba (Frontiers in Pediatrics, 2023)
Background Adequate children’s pain management is universally considered an ethical obligation. In evaluating and treating children’s pain, nurses invest more time and take a leading role. This study aims to evaluate the knowledge and attitudes of nurses towards the treatment of pediatric pain. Materials and Methods A total of 292 nurses working at four South Gondar Zone hospitals of Ethiopia was surveyed. To gather information from study participants, the Pediatric Nurses’ -Knowledge and Attitudes- Survey Regarding Pain (PNKAS) was employed. Frequency, percentage, mean, and standard deviation of the data were used for descriptive analysis, while Pearson correlation, one-way between-groups analysis of variance, and independent-samples t-test were used for inferential analysis. Results A large percentage of nurses (74.7%) lacked adequate knowledge and attitudes (PNKAS score <50%) for pediatric pain treatment. The mean ± SD accurate response score of 43.1% ± 8.6% was achieved by nurses. An increase in pediatrics nursing experience was significantly correlated with nurses’ PNKAS score (p < 0.001). The mean PNKAS scores of nurses who had official pain management training differed in a statistically significant way as compared to its counterpart (p < 0.001). Conclusion Nurses who are working South Gondar Zone of Ethiopia have insufficient knowledge and attitudes towards treatment of pediatric pain. Therefore, pediatric pain treatment in-service training is urgently needed.